2022
DOI: 10.56093/ijas.v92i9.106566
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fertigation studies in Nagpur mandarin (Citrus reticulata) grown on black clay soil

Abstract: A field experiment was conducted for four seasons (2013–17) on 12-year-old bearing Nagpur mandarin (Citrus reticulata Blanco) plants budded on rough lemon rootstock (Citrus jambhiri Lush) at ICAR-Central Citrus Research Institute, Nagpur, Maharashtra. Six zinc-based treatments, viz. S100 as soil application of ZnSO4 (100 g/plant), S200 as soil application of ZnSO4 (200 g/plant), S300 as soil application of ZnSO4 (300 g/plant, F100 as fertigation of ZnSO4 (100 g/plant), F200 as fertigation of ZnSO4 (200 g/plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…In addition, NPK are the most indispensable nutrients for the growth and development of coffee, similar to any other crop, as nitrogen is essential for coffee plants throughout the year, phosphorus is essential during the blossom period (flowering), and potassium is essential at the time of berry maturation, bean filling and hardening (Anonymous, 2014). The results of the present study are also in accordance with the findings of Venkataramanan (1988) and Shirgure et al (2001), who reported that fertigation increased the total number of branches and number of bearing nodes in coffee and in Nagpur mandarin, respectively. Vaidehi et al (2017) also reported that the increase in yield parameters under drip irrigation is due to better water utilization, minimum losses of water through percolation and evaporation, and an excellent soil–water–air relationship with higher oxygen in the root zone and higher uptake of nutrients.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, NPK are the most indispensable nutrients for the growth and development of coffee, similar to any other crop, as nitrogen is essential for coffee plants throughout the year, phosphorus is essential during the blossom period (flowering), and potassium is essential at the time of berry maturation, bean filling and hardening (Anonymous, 2014). The results of the present study are also in accordance with the findings of Venkataramanan (1988) and Shirgure et al (2001), who reported that fertigation increased the total number of branches and number of bearing nodes in coffee and in Nagpur mandarin, respectively. Vaidehi et al (2017) also reported that the increase in yield parameters under drip irrigation is due to better water utilization, minimum losses of water through percolation and evaporation, and an excellent soil–water–air relationship with higher oxygen in the root zone and higher uptake of nutrients.…”
Section: Discussionsupporting
confidence: 93%
“…In appropriate irrigation pursuits damage fruit quality by reducing nutrients uptake from the soil (Hutton et al, 2007 andQuiñones et al, 2007). Highest nutrient uptake and minimum nutrient filtrating were obtained by using modern irrigation arrangement (Shirgure and Srivastava, 2013). Such findings were found in our study, the maximum nutrient contents N, P and K in leaf of Manfalouty pomegranate were recorded for trees growing with 80% of the estimated amount of water compared with trees under 60 or 100% of estimated amount water.…”
Section: Discussionsupporting
confidence: 82%